Analisis Determinan Kejadian Diare pada Balita di Puskesmas Celikah Kota Kayuagung Kabupaten Oki - susilawati; Sari Murni, Nani; Harokan, Ali (Avicenna: Jurnal Ilmiah, 2025)
Background: The occurence of diarrhea in children at 2021 is around 1.22 billion in the world and approximately 3,350 children die every day. Out of the 15 Southeast Asian countries, Indonesia is ranked 12th in terms of diarrhea mortality in toddlers, with 8,600 deaths each year. This study aims to analyze the determinants of diarrhea incidence in the Celikah Health Center work area, Kayuagung City, Ogan Komering Ilir Regency from April to May 2024. Method: This study is quantitative with a cross-sectional design, the study population was 2533 toddlers, a sample of 96 respondents. The sampling technique is purposive sampling. Data analysis is univariate, bivariate, and multivariate tests. Results : The results of the statistical test analysis using the Chi-Square statistical test and multiple logistic regression. From the results of the multivariate statistical test, the dominant factor in the incidence of diarrhea was education (p = 0.000; OR = 6.568). Conclusion : The results of the study showed a significant relationship between the age of respondents, nutritional status of children, occupation, education, attitude, and clean water sources with the incidence of diarrhea. Keywords : Diarrhea, Determinants, Public Health Centers